Answer:
-1[4 + (-4)]
Explanation:
So first we need to evaluate the original expression, -1(0) = 0 since this is equivalent to saying negative one times zero is zero.
Now let's look at the options.
-1[4 + (-4)] evaluates using order of operations and the distributive property to -1[0] = 0. Notice this is the same as our original expression.
-1[4 + (4)] evaluates to -1[8] = -8. Note, this is different from the original expression.
1 + [4 + (-4)] evaluates to 1 + [0] = 1. Note this is different from the original expression.
-1[-4 + (-4)] evaluate to -1[-8] = 8. Note this is different from the original expression.
So we want to choose the first option which matches the original expression.
Cheers.